1 / 9

110 likes | 163 Vues

Algebra. 7.3 Solving Linear Systems by Linear Combinations. This is the third and final way to solve linear systems. The other two are ____________ and ______________. graphing. substitution. Steps. Arrange the equations with like terms in columns.

Télécharger la présentation
## Algebra

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Algebra**7.3 Solving Linear Systems by Linear Combinations**This is the third and final way to solve linear systems.**• The other two are ____________ and ______________. graphing substitution**Steps**• Arrange the equations with like terms in columns. • Multiply one or both equations by a number to obtain coefficients that are opposites for one variable. • Add the equations. One variable will be eliminated. Solve for the other. • Substitute this number into either original equation and solve for the other variable. • Check.**-2x + 2y = -8**2x + 6y = -16 8y = -24 y = -3 2x + 6y = -16 2x + 6(-3) = -16 2x – 18 = -16 2x = 2 x = 1 Solution: (1, -3) Solve Check: -2(1) + 2(-3) = -8 2(1) + 6(-3) = -16**3x = -6y + 12**-x + 3y = 6 Rewrite the top: 3x + 6y = 12 -x + 3y = 6 -3x + 9y = 18 15y = 30 y = 2 -x + 3y = 6 -x + 3(2) = 6 -x + 6 = 6 -x = 0 x = 0 Solution: (0, 2) Solve [ ]3 Check: 3(0) = -6(2) + 12 -(0) + 3(2) = 6**3x + 5y = 6**-4x + 2y = 5 -12x + 6y = 15 26y = 39 y = 39/26 y = 3/2 -4x + 2(3/2) = 5 -4x + 3 = 5 -4x = 2 x = -½ Answer: (-½, 3/2) Solve 12x + 20y = 24 [ ]4 [ ]3 Check: 12(-½) + 20(3/2) = 24 -4(-½) + 2(3/2) = 5**2x + 8y = -2**5x + 4y = 3 -10x - 8y = -6 -8x = -8 x = 1 2(1) + 8y = -2 2 + 8y = -2 8y = -4 y = -½ Answer: (1, -½) You try! Solve. [ ]-2 Check: 2(1) + 8(-½)= -2 5(1) + 4(-½) = 3**A boat traveled from 24 miles downstream in 4 hours. It**took the boat 12 hours to return upstream. Find the speed of the boat in still water(B) and the speed of the current(C). Speed in still water + current speed = speed downstream Speed in still water – current speed = speed upstream B + C = 6 mph B – C = 2 mph 2B = 8 mph B = 4 mph 4 mph + C = 6 mph C = 2 mph The boat goes 4 mph. The current goes 2 mph. Speed downstream is 24 miles/4 hours = 6 mph Speed upstream is 24 miles/12 hours = 2 mph**HW**P. 414-415 (#9-41 4X) (#45-48)

More Related